ULASAN SINGKAT MENGENAI "CHAMARREO""”TARIAN RAKYAT DARI MEXICO - Hernández, Angela María Vela (Imaji: Jurnal Seni dan Pendidikan Seni, 2019)
Makalah ini membahas tentang tarian rakyat tradisional dari Meksiko yang bernama "Chamarreo". Untuk memahami dari mana tarian Chamarreo berasal, karya ini menjelaskan latar belakang sejarah tarian Meksiko. Terdapat juga ulasan singkat tentang beberapa tarian tradisional rakyat dari utara, tengah dan selatan Meksiko. Ini adalah ringkasan untuk memahami beberapa karakteristik tarian Chamarreo seperti: koreografi, kostum, objek, musik, bentuk dan ketika pertunjukan tariannya berlangsung. Kata Kunci: abstrak, bold, italic, maksimal lima kata/frase, tata tulis A SHORT REVIEW OF "CHAMARREO" FOLK DANCE FROM MEXICO Abstract This paper talks about the traditional-folk dance from Mexico which name is "Chamarreo". In order to understand where the Chamarreo dance comes from, this work explained the historical background of Mexican dances. Also is a short review of some folk-traditional dances from north, central and southern Mexico. It is a summary to understand some of the characteristics of the Chamarreo dance such as: choreography, costume, object, music, form and when its dance performances take place. Keywords: abstract, bold, italic, maximum five words/phrases, template